Pengaruh Penambahan Kangkung dan Kacang Hijau Pada Nugget Lele Sebagai Sumber Protein dan Zat Besi - Nurdini, Dahlia; Fitriyanti, Rita; Pustikasari, Atikah; Auliannisa, Damaranti; Pratiwi, Kartika (Jurnal Ilmiah Kesehatan, 2025)
Catfish has long been a popular fishery commodity among Indonesians (Santoso, S., Yanti, WS, & Manajemen, E. 2019). This research is an experimental study conducted in May 2024 at the nutrition laboratory of MH. Thamrin University and will be continued at the DKI Jakarta Regional Health Laboratory in September 2024. This study involved 25 undergraduate students of Nutrition at MH. Thamrin University, Jakarta, as panelists. This study used a Completely Randomized Design (CRD) with 3 different treatments and 2 replications. The data were processed using SPSS using the Analysis of Variance (ANOVA) test and will be continued to the Duncan's Multiple Range Test, if there is a significant difference in the ANOVA test. This study shows that the addition of kale and green beans affects the organoleptic quality of catfish nuggets, especially in the aspects of color, taste, and texture. However, there is no significant effect on aroma. The panelists' level of preference for color, taste, aroma, and texture also increased, although not significantly in the overall assessment. The best product was obtained in treatment P1 (10% kale and 20% mung beans). It is recommended that further research examine the product's shelf life, use fresh catfish without steaming, and apply an egg coating to prevent the breading from coming off easily. Keywords: Catfish, organoleptic, nuggets